2011
DOI: 10.1007/s10495-011-0613-1
|View full text |Cite
|
Sign up to set email alerts
|

The microtubule depolymerizing agent naphthazarin induces both apoptosis and autophagy in A549 lung cancer cells

Abstract: Naphthazarin (DHNQ, 5,8-dihydroxy-l,4-naphthoquinone) is a naturally available 1,4-naphthoquinone derivatives. In this study, we focused on elucidating the cytotoxic mechanism of naphthazarin in A549 non-small cell lung carcinoma cells. Naphthazarin reduced the A549 cell viability considerably with an IC(50) of 16.4 ± 1.6 μM. Naphthazarin induced cell death in a dose- and time-dependent manner by activating apoptosis and autophagy pathways. Specifically, we found naphthazarin inhibited the PI3K/Akt cell surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 48 publications
2
61
2
2
Order By: Relevance
“…The results of the present study revealed that naphthazarin promoted Bax expression and inhibited Bcl-2 protein expression, and increased caspase-3 activation in SW480 cells. These results are in accordance with those of Acharya et al (9) who reported that naphthazarin increases the Bax/Bcl-2 protein ratio in A549 lung cancer cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study revealed that naphthazarin promoted Bax expression and inhibited Bcl-2 protein expression, and increased caspase-3 activation in SW480 cells. These results are in accordance with those of Acharya et al (9) who reported that naphthazarin increases the Bax/Bcl-2 protein ratio in A549 lung cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…Naphthazarin is an important active ingredient, which exhibits extensive pharmacological activities, including antitumor activity, and due to its low toxicity, it has gained considerable attention (9,10). However, to date the anticancer effects of naphthazarin on human colorectal cancer cells have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, at least part of the cytotoxic effect of the MT-stabilizer Taxol is dependent on its ability to block autophagosome maturation (Veldhoen et al, 2012). Conversely, other tubulin-binding drugs, such as vinblastine, naphtharazin or 2-methoxyestradiol, might instead stimulate autophagy, which could contribute to their anticancer activity (Acharya et al, 2011;Chen et al, 2008;Kamath et al, 2006;Köchl et al, 2006;Lorin et al, 2009). In the context of neurodegenerative diseases, the link between MT-acting drugs and autophagy could also prove to be important.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is the process of sequestering cytoplasmic proteins into the lytic component and is characterized by the formation and promotion of acidic vesicular organelles (AVOs) (Acharya et al, 2011;Wang et al, 2012). To detect the development of AVOs, A549 cells were treated with various concentrations of HBC for different lengths of time, and then cells were stained with acridine orange (5 mg/mL) for 40 s at room temperature.…”
Section: Acridine Orange Stainingmentioning
confidence: 99%
“…During authophagy, autophagosomes fuse with lysosomes to form autophagolysosomes (Acharya et al, 2011;Wang et al, 2012). Autophagolysosomes could be dyed by acridine-orange which produced the red fluorescence.…”
Section: Hbc Induced Acidic Vacuole Formation In A549 Cellsmentioning
confidence: 99%